Epidemiology of personality disorders in individuals with gender dysphoria - Furlong, Yulia; Janca, Aleksandar (Wolters Kluwer Health, 2022)
Purpose of review Prevalence estimates of personality disorders (PD) in individuals with gender dysphoria (GD) are variable and heterogeneous, as psychiatric comorbidity and long-term follow-up data from gender-diverse samples are still limited. This review aims to assess prevalence rates across age groups and discuss potential reasons for variability in PD prevalence estimates among transgender people. Recent findings International epidemiological data from several countries indicate that the best available estimates of the prevalence of any PD diagnosis in transgender youth are around 20% for adolescents and tend to increase to nearly 50% in trans-adults. The paucity of available data on personality dysfunction in children and adolescents with GD precluded us from definitive conclusions on the trends of emerging PDs in this population. Estimates of PD prevalence in transgender and gender-diverse people seem to be highly affected by methodological characteristics of the studies with no universally agreed reference standards for this population. Summary The review of epidemiological studies on PD among gender-diverse people highlights the need for using more standardized study methodologies to make findings comparable. Nevertheless, international epidemiological data seem to support the link association between the development of PD and GD. Keywords gender dysphoria, gender identity disorder, gender incongruence, personality disorders, transgender and gender-diverse people, transsexualism